PbTe quantum dots highly packed monolayer fabrication by a spin coating method - Svetlana Lyssenko; Michal Amar; Alina Sermiagin; Refael Minnes (PLoS ONE, 2025)
This study investigates the fabrication of large-area, highly-ordered monolayers of PbTe quantum dots (QDs) on TiO2/ITO substrate, using a fast, simple, and repeatable spin-coating technique. For the first time, a real monolayer (a layer with the height of a single QD) covering approximately 3 cm2 was successfully prepared, achieving a root-mean-square roughness (Rq) of 1.37 nm. The research systematically explores key parameters such as QD morphology, concentration, spin-coating conditions, substrate characteristics, wetting properties, and solvent effects to optimize thin film deposition. The findings reveal that the spin-coating method favors the formation of layers with spherical QDs (6–9 nm) over cubical QDs (10–13 nm). The findings highlight the significant influence of solvent evaporation rate, viscosity, and wettability on monolayer quality. Chloroform was identified as the optimal solvent for cubical QDs (~90% coverage), while hexane was more effective for spherical QDs (90%-100% coverage). Beyond monolayers, high-quality bilayers were also fabricated, demonstrating the method’s potential for multilayer fabrication. This rapid and efficient method for monolayer and bilayer fabrication marks a significant breakthrough in producing uniform, large-area films, facilitating seamless integration with existing technologies. It offers a scalable and cost-effective solution, opening the door to broader applications in fields that demand high-quality thin film deposition.